Gas diffusion layer, preparation method and application thereof and proton exchange membrane electrolytic cell

By preparing TiCN coating on the surface of Ti-based gas diffusion layer, the problem of passivation of Ti-based gas diffusion layer in electrolytic water is solved, high conductivity and corrosion resistance in electrolytic water environment is achieved, and the required electrolysis is reduced Voltage and provide low-cost solutions suitable for large-scale electrolytic hydrogen production processes.

CN119265587APending Publication Date: 2025-01-07TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411219594.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing Ti-based gas diffusion layer passivates due to excessive electrolysis potential during the electrolysis process, forming a surface passivation layer, reducing conductivity, increasing the voltage required for electrolysis, and the precious metal coating is high, making it difficult to be applied to industrial applications. Mass production.

Method used

The TiCN coating is prepared on the surface of the Ti-based gas diffusion layer. It is prepared by cleaning, impregnation, sintering and other steps. The mass proportion of the TiCN coating is 5%-10%, the sintering temperature is 320-350℃, and the time is 3-3.5 hours , used to form a protective layer that is corrosion-resistant and conductive.

Benefits of technology

It effectively prevents passivation of Ti substrate, maintains good conductivity and corrosion resistance, reduces the voltage required for electrolysis, and is low in cost. It is suitable for large-scale electrolysis hydrogen production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265587A_ABST
    Figure CN119265587A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrolytic cells, and particularly relates to a gas diffusion layer, a preparation method and application thereof and an electrode. The gas diffusion layer comprises a Ti-based gas diffusion layer substrate and a TiCN coating arranged on the surface of the Ti-based gas diffusion layer substrate. According to the technical scheme, the TiCN coating is prepared on the surface of the Ti-based gas diffusion layer substrate (Ti substrate), the obtained new gas diffusion layer can effectively prevent the Ti substrate from being passivated in the electrolyzed water environment, good conductivity is kept, the main effect is that TiCN has good conductivity, high hardness and oxidation resistance, and after the TiCN is prepared into the coating, the corrosion resistance of the coating is greatly improved. The high-voltage high-voltage hydrolysis film can be kept stable in a high-voltage hydrolysis environment, and a Ti substrate on the inner layer is protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrolyzers, and in particular relates to a gas diffusion layer and a preparation method and application thereof, as well as a proton exchange membrane electrolyzer. Background Art

[0002] There are four main ways to produce hydrogen: fossil fuel hydrogen, industrial byproduct hydrogen, water electrolysis hydrogen, biomass hydrogen and others. Proton exchange membrane (PEM) water electrolysis is a clean and environmentally friendly hydrogen production process with high efficiency, high purity and pollution-free hydrogen production method.

[0003] The gas diffusion layer (GDL) is an important component of PEM-WE (ion exchange membrane-electrolyzer). Its main functions are: providing a path for the hydrogen and oxygen reaction gases to reach the cathode and anode catalyst layers (CL); providing a path for the generated water to be discharged; making the CL and the cathode and anode plates (BP) electrically connected; helping to dissipate some of the heat; and mechanically supporting the electrode assembly (MEA). Ti is widely used as a gas diffusion layer because of its high corrosion resistance, low density and excellent mechanical properties.

[0004] In the process of water electrolysis, over time, due to the excessively high electrolysis potential, the Ti-based gas diffusion layer will be passivated to form a surface passivation layer. Although this surface passivation layer can protect the Ti substrate from corrosion, it increases the resistance and reduces the conductivity of the gas diffusion layer GDL, thereby increasing the voltage required for electrolysis. Therefore, in the PEM-WE system, it is very important to avoid excessive passivation of the GDL and improve the utilization of energy.

[0005] At present, the common method to solve the transition passivation of Ti-based gas diffusion layer is to apply a precious metal (such as Au, Pt, IrO2, etc.) coating on the surface of Ti-based gas diffusion layer (Ti felt) as a protective layer to increase the conductivity and corrosion resistance of Ti felt under electrolysis conditions. However, due to the high price of precious metals, the cost of PEM electrolyzer system is increased, making it difficult to apply to large-scale industrial production. Therefore, it is very necessary to find a low-cost coating or surface treatment technology. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a gas diffusion layer and a preparation method and application thereof, as well as a proton exchange membrane electrolyzer.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A gas diffusion layer comprises a Ti-based gas diffusion layer substrate and a TiCN coating arranged on the surface of the Ti-based gas diffusion layer substrate.

[0009] The mass proportion of the TiCN coating in the gas diffusion layer is 5%-10%, preferably 5.13%-9.76%, and more preferably 8.23%-9.76%.

[0010] The present invention also includes a method for preparing the gas diffusion layer, comprising the following steps: 1) cleaning and drying a Ti-based gas diffusion layer substrate; 2) impregnating the treated Ti-based gas diffusion layer substrate in a TiCN suspension; and 3) drying and sintering the impregnated Ti-based gas diffusion layer substrate to obtain the desired gas diffusion layer.

[0011] The concentration of the TiCN suspension in step 2) is ≥24 g / L; preferably 24-48 g / L; more preferably 36 g / L; preferably, the average particle size of the TiCN is 1-10 μm; preferably 5 μm.

[0012] The sintering conditions of step 3) are nitrogen flow, sintering temperature of 320-350° C., sintering time of 3-3.5 h, heating rate of 3-5° C. / min, preferably 350° C., 3 h.

[0013] The specific steps of step 1) are: ultrasonically cleaning the Ti-based gas diffusion layer substrate with ethanol and deionized water respectively; preferably, the ultrasonic cleaning time is 15-20 minutes, preferably 20 minutes.

[0014] Preferably, the treated Ti-based gas diffusion layer substrate obtained in step 1) is corroded; preferably, a strong alkaline solution is used for corrosion; more preferably, the strong alkaline solution is a sodium hydroxide solution; preferably, the concentration of the sodium hydroxide solution is 6 mol / L; the corroded Ti-based gas diffusion layer substrate is washed with deionized water and then dried.

[0015] The present invention also includes an application of the gas diffusion layer, which is applied to the gas diffusion layer of a proton exchange membrane electrolyzer.

[0016] The present invention also includes a proton exchange membrane electrolyzer, comprising the gas diffusion layer.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The technical solution of the present application prepares a TiCN coating on the surface of a Ti-based gas diffusion layer substrate (referred to as a Ti substrate). The obtained new gas diffusion layer can effectively prevent the Ti substrate from passivation and maintain good conductivity in an electrolytic water environment. This is mainly due to the good conductivity, high hardness, and oxidation resistance of TiCN. After it is made into a coating, it can remain stable in a high-voltage hydrolysis environment to protect the inner Ti substrate. The gas diffusion layer preparation process involved in the present invention is simple and low in cost, and provides a new strategy for realizing large-scale electrolytic water hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The TiCN-coated, untreated, gold-sprayed and platinum-sprayed Ti-based GDLs obtained in Example 1 and Comparative Examples 1-3 were tested at 1.7 V. RHE The electrostatic potential polarization curve obtained by testing under a voltage of;

[0020] Figure 2 The electrochemical impedance spectroscopy (EIS) test results of Example 1 and Comparative Examples 1-3 at open circuit potential (OCP), within a frequency range of 100 kHz to 10 mHz, with a disturbance amplitude of 10 mV, and an equivalent circuit diagram of the EIS data;

[0021] Figure 3 The experimental test results of the interface contact resistance of Example 1 and Comparative Example 1 before polarization;

[0022] Figure 4 150N cm -2 Experimental test results of the interface contact resistance of Example 1 and Comparative Example 1 before and after the polarization test under pressure of 5h;

[0023] Figure 5 ICR (150 N cm) of Example 1 before and after polarization for 100 h -2 ) test results. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0025] Example 1

[0026] A method for preparing a gas diffusion layer (GDL), comprising the following steps:

[0027] (1) A Ti-based GDL (Ti felt, thickness 0.3 mm-0.5 mm, porosity 55%-70%, purchased from Suzhou Shengernuo Technology Co., Ltd.) was taken as the Ti-based gas diffusion layer substrate and placed in ethanol and deionized water, respectively, ultrasonically cleaned for 20 minutes, and then dried at 60°C in a constant temperature drying oven for 6 hours;

[0028] (2) In order to remove the oxide film on the surface of the Ti felt and make the Ti-based GDL skeleton have more porous structures, a 6 mol / L NaOH solution was prepared and the dried Ti-based GDL was immersed in the NaOH solution for 24 h; the immersed Ti-based GDL was taken out and ultrasonically cleaned in deionized water for 20 minutes and dried;

[0029] (3) The TiCN powder is further ground in a mortar to an average particle size of 1-10 μm, preferably 5 μm, and the ground powder is mixed with deionized water to form a 48 g / L TiCN suspension, which is stirred with a magnetic stirrer for 1 h.

[0030] (4) Immerse the treated Ti-based GDL in the TiCN suspension for 24 h. Take out the soaked Ti-based GDL and dry it at 60 °C for 6 h;

[0031] (5) After drying, the resulting product was placed in a tube furnace and heated at 350 °C for 3 h to obtain a TiCN-coated Ti-based GDL.

[0032] Example 2

[0033] The difference between Example 2 and Example 1 is that the soaking time of the NaOH solution is different, and the soaking time is changed from 24 hours to 8 hours.

[0034] Example 3

[0035] The difference between Example 3 and Example 1 is that the soaking time of the NaOH solution is different, and the soaking time is changed from 24 hours to 18 hours.

[0036] Example 4

[0037] The difference between Example 4 and Example 1 is that the concentration of the TiCN suspension used for immersion is different, that is, the immersion concentration is changed from 48 g / L to 24 g / L.

[0038] Example 5

[0039] The difference between Example 5 and Example 1 is that the concentration of the TiCN suspension used for soaking is different, that is, the soaking concentration is changed from 48 g / L to 36 g / L.

[0040] Example 6

[0041] The difference between Example 6 and Example 1 is that the sintering temperature in the tubular furnace is different, and the sintering temperature is changed from 350°C to 300°C.

[0042] Example 7

[0043] The difference between Example 7 and Example 1 is that the sintering temperature in the tubular furnace is different, and the sintering temperature is changed from 350°C to 400°C.

[0044] Example 8

[0045] The difference between Example 8 and Example 1 is that step (2) is not included, that is, NaOH corrosion is not performed.

[0046] Comparative Example 1

[0047] The difference between Comparative Example 1 and Example 1 is that no treatment is performed on the Ti-based GDL.

[0048] Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 1 is that only steps (1) to (3) in the example are performed, and after step (3), gold is sprayed for 90 seconds using an ion sputtering apparatus at a current of 15 mA.

[0050] Comparative Example 3

[0051] The difference between Comparative Example 3 and Example 1 is that only steps (1) to (3) in the example are performed, and after step (3), platinum is sprayed for 90 seconds using an ion sputtering apparatus at a current of 15 mA.

[0052] The interfacial resistance (ICR) of test examples 1-7 and comparative examples 1-3 was tested, and the electrochemical performance was tested in a PEM-WE electrolysis environment;

[0053] The performance test specifically includes the following steps:

[0054] Electrochemical tests were performed using a three-electrode system controlled by an electrochemical workstation: (1) at 1.7 V RHE (2) Electrochemical impedance spectroscopy (EIS) was performed at an open circuit potential (OCP) of 100 kHz to 10 mHz with a perturbation amplitude of 10 mV. RHE The CA curve of polarization for 5h was tested in 0.5M H2SO4+2ppm HF solution at a voltage of .

[0055] Interface contact resistance test: (1) Test different pressures (50-250N cm -2) under polarization; (2) ICR before and after polarization for 5 h (150 N cm -2 ); (3) Test the ICR (150N cm) of Example 1 before and after polarization for 100h -2 ).

[0056] Figure 1 The TiCN-coated Ti-based GDL obtained in Example 1 and the untreated, gold-sprayed, and platinum-sprayed Ti-based GDLs obtained in Comparative Examples 1-3 are shown in Figure 1. RHE The electrostatic potential polarization curve obtained by testing under a voltage of , the corrosion current density of Example 1 is 0.37uA cm -2 The corrosion potential is 0.54V RHE The corrosion current density of the untreated Ti-based GDL in Comparative Example 1 was 9.09 uA cm -2 , the corrosion potential is 0.1V RHE The corrosion current density of the gold-sprayed Ti felt in Comparative Example 2 is 1.19uAcm -2 , the corrosion potential is 0.62V RHE ; The corrosion current density of the platinum-sprayed Ti felt in Comparative Example 3 is 5.9uAcm -2 , the corrosion potential is 0.76V RHE This shows that compared with the untreated Ti-based GDL, the corrosion potential of the coated Ti-based GDL is significantly improved, the corrosion current density is significantly reduced, the protection ability of the Ti felt is enhanced, the corrosion rate is reduced, and the corrosion resistance is significantly improved; at the same time, compared with the precious metal coating, the TiCN coating has better corrosion resistance.

[0057] Figure 2 The electrochemical impedance spectroscopy (EIS) test results of the fitting embodiment 1 and comparative examples 1-3 at open circuit potential (OCP), frequency range of 100kHz to 10mHz, and disturbance amplitude of 10mV are shown, as well as the equivalent circuit of the EIS data. s is the solution resistance, CPE1 is the constant phase element, R c are the coating capacitance and resistance, R ct is the charge transfer resistance between the coating interface and the substrate, and CPE2 is the double layer capacitance. The semicircle diameter of the Nyquist plot of Comparative Example 1 is smaller than that of Example 1 and Comparative Examples 2 and 3, and the semicircle diameter of Example 1 is the largest. This indicates that the Ti-based GDL loaded with TiCN coating has a higher R ct , lower corrosion rate and higher corrosion resistance.

[0058] Figure 3The experimental test results of the interface contact resistance are shown. It can be seen that within the experimental pressure range, the interface contact of Example 1 is greater than that of Comparative Example 1, which indicates that the interface contact resistance of the Ti-based GDL loaded with the TiCN coating is significantly reduced relative to the untreated Ti-based GDL.

[0059] Figure 4 Demonstrated 150N cm -2 The experimental test results of the interface contact resistance before and after the polarization test under the pressure of 150N cm -2 The contact resistance of Comparative Example 1 is 2.59 mΩ·cm 2 The contact resistance of Example 1 is 1.73 mΩ·cm 2 After 5 h of constant potential polarization at 150 N cm -2 The contact resistance of Example 1 is 2.13 mΩ·cm 2 There is no obvious increase; however, the contact resistance of Comparative Example 1 increased significantly, reaching 4.85 mΩ·cm 2 This indicates that the TiCN coating can improve the conductive properties of Ti-based GDLs, effectively inhibit the passivation of the Ti felt substrate, and improve the operating stability.

[0060] Figure 5 The ICR (150 N cm) of Example 1 before and after polarization for 100 h is shown. -2 ) test results. After polarization for 100h, the interface contact resistance of the Ti-based GDL loaded with TiCN coating increased from 1.73mΩ·cm 2 Increased to 2.51 mΩ·cm 2 (150N cm -2 ), which is still lower than the contact resistance of Comparative Example 1 before polarization. It can be seen that through the 100h contact resistance test, the Ti-based GDL loaded with TiCN coating still has a high conductivity.

[0061] The results of other embodiments are shown in Table 1. It can be seen from Examples 1-3 in Table 1 that the immersion time in NaOH solution affects the amount of nanopore corrosion on the Ti-based GDL skeleton. When the immersion time is within a certain range, the longer the immersion, the more nanopores etched on the Ti-based GDL skeleton, which is more conducive to the entry of TiCN molecules to form a coating.

[0062] It can be seen from Examples 1, 5, and 6 that within a certain TiCN immersion concentration range, the higher the immersion concentration, the more uniform the TiCN coating formed on the surface, and the better the corrosion resistance and conductivity. When the immersion concentration reaches a certain range, the effect of increasing the concentration on the performance of the coating will become very weak.

[0063] It can be seen from Examples 1, 6, and 7 that within a certain sintering temperature range, the effect of sintering temperature on coating performance is very small and can be almost ignored. Therefore, Example 1 with NaOH soaking time of 24h, TiCN soaking concentration of 48g / L, and sintering temperature of 350 degrees is selected as a preferred embodiment for illustration.

[0064] Table 1

[0065]

[0066] From the above, it can be seen that the technical solution of the present application prepares a TiCN coating on the surface of a Ti-based gas diffusion layer substrate (Ti substrate), and the obtained new gas diffusion layer can effectively prevent the Ti substrate from passivation and maintain good conductivity in an electrolytic water environment. This is mainly due to the good conductivity, high hardness, and oxidation resistance of TiCN. After it is made into a coating, it can remain stable in a high-voltage hydrolysis environment to protect the inner Ti substrate. The gas diffusion layer preparation process involved in the present invention is simple and low in cost, and provides a new strategy for realizing large-scale electrolytic water hydrogen production.

[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A gas diffusion layer, characterized in that: The invention comprises a Ti-based gas diffusion layer substrate and a TiCN coating arranged on the surface of the Ti-based gas diffusion layer substrate.

2. The gas diffusion layer according to claim 1, characterized in that The mass proportion of the TiCN coating in the gas diffusion layer is 5%-10%, preferably 5.13%-9.76%, and more preferably 8.23%-9.76%.

3. A method for preparing a gas diffusion layer according to claim 1 or 2, characterized in that: The following steps: 1) cleaning and drying the Ti-based gas diffusion layer substrate; 2) impregnating the treated Ti-based gas diffusion layer substrate in a TiCN suspension; 3) drying the impregnated Ti-based gas diffusion layer substrate and sintering it to obtain the desired gas diffusion layer.

4. The preparation method according to claim 3, characterized in that: The concentration of the TiCN suspension in step 2) is ≥24 g / L; preferably 24-48 g / L; more preferably 36 g / L; preferably, the average particle size of the TiCN is 1-10 μm; preferably 5 μm.

5. The preparation method according to claim 3, characterized in that: The sintering conditions of step 3) are nitrogen flow, sintering temperature of 320-350° C., sintering time of 3-3.5 h, heating rate of 3-5° C. / min, preferably 350° C., 3 h.

6. The preparation method according to claim 3, characterized in that: The specific steps of step 1) are: ultrasonically cleaning the Ti-based gas diffusion layer substrate with ethanol and deionized water respectively; preferably, the ultrasonic cleaning time is 15-20 minutes, preferably 20 minutes.

7. The preparation method according to claim 3, characterized in that: The treated Ti-based gas diffusion layer substrate obtained in step 1) is corroded; preferably, a strong alkaline solution is used for corrosion; more preferably, the strong alkaline solution is a sodium hydroxide solution; preferably, the concentration of the sodium hydroxide solution is 6 mol / L; the corroded Ti-based gas diffusion layer substrate is washed with deionized water and then dried.

8. Use of the gas diffusion layer according to claim 1 or 2, characterized in that: Applied to gas diffusion layer of proton exchange membrane electrolyzer.

9. A proton exchange membrane electrolyzer, characterized in that: Comprising the gas diffusion layer according to claim 1 or 2.